Analisis Topografi Panel Bulu Ayam Sebagai Material Dinding - Ansarullah Faharuddin; Mukhtar Thahir Sarkawi; Sriwijanaka Hartono (Universitas Muslim Indonesia, 2022)
Chicken meat, we consume has feathers and is a waste, if it is not processed it can result in environmental pollution. Chicken slaughter waste produces an average featherweight of 4-9% of live weight, so technology and methods are needed to reduce threats to the environment. The potential of chicken feathers has been used to fill pillows, make feather dusters and accessories, and is still underutilized as wall material, so researchers will develop the process into wall panel material, applying it to the field of architecture. The purpose of the research is chicken feather waste, which will be processed and developed into a building wall material, so it is necessary to investigate and analyze the surface topography of the panel before it is applied as a wall material. Previous research has known that the density value of chicken feather panels is 0.4, the category of rigid soft fiberboard material. The material scanning engineering method is carried out in the Microstructure laboratory to determine the surface topography of the material before it is applied as a wall material. The results of testing the chicken feather panel material can be recommended as a new alternative material in the architectural field.